Whole-plant corn silage treated with Azospiriullum sp., Bradyrhizobium sp. or Bacillus sp. compared with commercial inoculants - Nazato, Larissa Maniero (2024)
Investigating non-traditional microorganisms utilized in agricultural contexts for diverse productive and health-related objectives, and their adaptability to a silage setting, offers a route to advance conservation technologies in silage production. Therefore, two trials were conducted to evaluate the fermentation patterns in corn silages treated Bacillus sp., Azospirillum sp., and Bradyrhizobium sp., in contrast to control silages or those treated with commercially available inoculants containing homo or heterolactic Lentilactobacillus strains. In Phase 1, the harvested forage was divided into seven parts for each of the seven treatments in Experiment 1 and eight parts for each of the eight treatments in Experiment 2. Each part was subdivided into four piles and treated separately with the inoculant to create four replicates for each treatment. From each pile, two silos of 20 liters were produced (each designated for a specific opening time of 45 days or 90 days), and 3 mini-bags of approximately 500g each were prepared to study the silage acidification dynamics over time (6,12 and 24 hours). The silos were labeled R1 to R4, and the mini-bags R1 to R3. For Phase 2, the harvest forage was divided in the same way, but into eight parts for each of the eight treatments. Each part was subdivided into three piles and treated separately with the inoculant to create three replicates for each treatment. From each pile, two silos of 20 liters were produced (each designated for a specific opening time of 45 days or 90 days), and three mini-bags. The silos were labeled R1 to R3, and the mini-bags R1 to R3. The chemical composition, fermentation characteristics, chromatography, microbial count and aerobic stability were analyzed. Data were analyzed using the MIXED procedure of SAS and the Tukey-Kramer significance test (P<0.05) was applied for Treatment, Time, and Treatment*Time interaction. In this experiment, in the first 6 hours, the control has the highest pH and the strains resemble LP and LB treatments, the last one with the lowest value. Chemical composition, fermentation characteristics and chromatography, microbial count, and aerobic stability were analyzed. In phase 1, the experiment was conducted over two days, designated as Experiment 1 and Experiment 2. In Experiment 1 were utilized the Azospirillum brasiliense (ABV5, ABV6) and Bradyrhizobium elkanii semia (BV36, BV27) and in Experiment 2, the Bacillus subitilis (BV02, BV09, BV30, BV31) and Bacillus sp. (BV26) and in both experiments, the inoculants were compared with a control treatment (CONT) and with Lactiplantibacillus plantarum (LP) and Lentilactobacillus buchneri (LB). In Experiment 1, after 45 days of storage, the LB treatment showed the highest pH compared to the other treatments (3.85 vs 3.70% DM). The same pattern was observed after 90 days of storage, with ABV5, ABV6, BV36, and BV37 also exhibiting similarly high pH concentrations. Among the bacterial populations, the LB treatment revealed the highest count for LAB (8.20 vs. 6.10 log cfu.g-1), followed by LP (7.29 vs. 6.25 log cfu.g-1). The Bradyrhizobium and Azospiriullum treatments did not differ from the control treatment for other fermentation characteristics and aerobic stability. In Experiment 2, lactic acid (LA) contents demonstrated an interaction between additives and storage time. When considering time within additives, all treatments exhibited an increase in LA contents, except for LB treatment which remained unchanged. Examining additives within time, at 90 days, new strains BV09 and BV26 had the highest contents, with BV02, BV30, BV31, and LP displaying similarities to them, as well as to the Control treatment, and LB treatment had the lowest content. The LEV displayed a decline in the count when considering the impact of time (4.04 to 3.44 log cfu.g-1). The LP treatment yielded the highest count (5.03 vs 3.55 log cfu.g-1), while the lowest was observed in the LB treatment (<2.00 vs 3.99 log cfu.g-1). The remaining treatments exhibited similarities to the Control. Regarding ethanol, a significant interaction was observed (P value < 0.001). Considering time within additives, Control and LP exhibited an increase, while the other treatments remained consistent. Analyzing additives within time, at 45 days, LP displayed the highest content (0.68 vs. 0.11 % of DM correction), with the others being lower and similar among themselves. At 90 days, LP again showed the highest content, followed by Control, while BV09 and BV30 exhibited the lowest contents. The aerobic stability increased from 45 days to 90 days (38.5 vs. 49.0 hours). Among the additives, LB exhibited the longest duration (64.4 vs. 40.7 hours), followed by LP (50.8 vs. 42.7 hours). BV09, BV26, and BV30 showed similarity in stability to LP and Control treatments. However, BV02 and BV31 were only comparable to the control, which demonstrated the lowest aerobic stability. The aerobic stability of the silages did not differ from the control treatment; however, the Bacillus strains showed promise in controlling yeast metabolism. In phase 2, the harvested forage was treated with Bacillus sp. inoculants (BV02, BV09, BV26, BV30, and BV31) and commercial lactobacillus-based inoculants (Lentilactobacillus buchneri LB and Lactiplantibacillus plantarum LP). For LA variable, the additives treatments showed differences only inside 12h and the highest contents were found for LP (0.29 vs. 0.87 % of MScorr). For 90d of storage, the treatments BV02, BV09, BV26 and BV30 had the highest values for LA (5.09, 4.94, 5.19, 5.05 vs. 2.58 % of DMcorr, respectively). The growth of BAL was favored because the Bacillus trial counts were greater than 4 log cfu/g for the treatments. Strains BV02 (166h) and BV30 (174h) had similar aerobic stability as LB treatment (216h), and strain BV09 (140h) presented longer aerobic stability than the Control (70.3h). LB treatment in 45 days of storage presented the highest acetic acid contents (1.08 % of DMcorr) and bacillus treatment had the same behavior as the control, except by BV31 equalized as LP. For 90 days of storage, BV09 was statistically equal to LB treatment (0.8 vs 1.08 % DM Corr) but the other bacillus treatments had similar values as the Control and LP. LB treatment had the highest quantities of propionic acid (0,1% DMcorr) and LP, the lowest (0.009% DM). The other treatments had intermediate contents but the bacillus rehearsals that showed similar aerobic stability as LB, such as BV02, BV09, and BV30 demonstrated high quantities of this acid (0.04, 0.06, and 0.01% DMcorr, respectively). The silages produced under inoculation with Bacillus strains integrated desirable quality fermentation characteristics and aerobic deterioration control.